Pengaruh Polyethylene Fiber pada Material Resin Komposit terhadap Jumlah Koloni Candida albicans - Raymund Octavius Kusuma Buwana; Widowati Siswomihardjo; Siti Sunarintyas (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Fiber reinforced composite (FRC) is a material combination of polymer matrix and fiber. Fiber that commonly used in dentistry is polyethylene fiber due its resistance to abrasion. During placement of FRC in mouth, interaction will occur between the material with mucosa, saliva, and microorganisms. Candida albicans is one of many microorganisms present in oral. The purpose of this study was to determine the effect of addition polyethylene fiber on composite resin to C. albicans colony counts. Flowable composite and polyethylene fiber are material used in this study. Bar-shaped samples which sized 5x4x2 mm (n=4) immersed in 5 ml saliva for 1 hour, then immersed in suspension containing C. albicans and incubated for 2 hours at 37°C. The suspension was diluted to 10 then 0.1 mL were put in a solid medium and incubated for 48 hours at 37°C. The amount of C. albicans was determined by direct count. Data were statistically analyzed by using unpaired t-test.The result of unpaired t-test showed a significance differences of C. albicans colony between composite resin and FRC with polyethylene fiber (p <0.05). The conclusion was there was a significant increasing number of C. albicans colonies on composite resin with addition of polyethylene fiber.